Adult sex ratio and social status predict mating and parenting strategies in Northern Ireland. (31st July 2017) - Uggla, Caroline; Mace, Ruth
Abstract : Evidence from animal species indicates that a male-biased adult sex ratio (ASR) can lead to higher levels of male parental investment and that there is heterogeneity in behavioural responses to mate scarcity depending on mate value. In humans, however, there is little consistent evidence of the effect of the ASR on pair-bond stability and parental investment and even less of how it varies by an individual's mate value. In this paper we use detailed census data from Northern Ireland to test the association between the ASR and pair-bond stability and parental investment by social status (education and social class) as a proxy for mate value. We find evidence that female, but not male, cohabitation is associated with the ASR. In female-biased areas women with low education are less likely to be in a stable pair-bond than highly educated women, but in male-biased areas women with the lowest education are as likely to be in a stable pair-bond as their most highly educated peers. For both sexes risk of separation is greater at female-biased sex ratios. Lastly, our data show a weak relationship between parental investment and the ASR that depends on social class. We discuss these results in the light of recent reformulations of parental investment theory. This article is part of the themed issue 'Adult sex ratios and reproductive decisions: a critical re-examination of sex differences in human and animal societies'.